Gender & kepimpinan dalam kalangan pelajar wanita di universiti awam - Zaharah Hassan,; Abu Daud Silong, (Universiti Kebangsaan Malaysia, 2008)
The number of females appointed to leadership positions is small compared to males. This phenomenon happens not only in developing countries but also in developed nations. Various barriers are mentioned and this includes limited educational opportunities for females. However, in Malaysia, the numbers of females in institutions of higher learning far exceed the number of males in the ratio of 70:30. Does this mean that the number of female students selected as leaders in universities will also increase? This paper will explore the question related to the position of female students in students’ associations in one public university. Data are obtained through document analysis, focus group interviews and in-depth interviews with students involved in associations. The questions attempted to be answered include the number of female students involved in associations; the leadership positions held; factors that motivate and prevent them from participating; and the challenges faced by them. The analysis shows that there are many female students appointed asrepresentatives in associations but the numbers holding the positions of President are disappointing. What are the factors contributing to this situation? Further, several recommendations will be discussed to assist students in improving their leadership skills